Contextualizing multimedia semantics towards personalised eLearning - Eze, E.; Ishaya, T.; Wood, D.M. (Journal of Digital Information Management, 2007)
Recent developments of the Internet and the World Wide Web (WWW) have resulted in the proliferation of multi-media, resources and learning with existing multimedia web resources on the Web is becoming more prevalent and important. While recent standardization efforts in eLearning such as LOM, SCORM, and IMS Learning Design work towards learning content description, packaging, and delivery; existing eLearning solutions still lack the ability to adequately use multi-media resources to provide a learner with personalised learning resources. Effective use of multimedia for web-based learning provides quality interactive learning experience, but current techniques does not adequately provide a semantic approach for organising multimedia resources. With evolving trend in learning through the use of web technology, eLearning systems are expected to provide personalised learning resources for effective learning. We have accordingly proposed a way of organising existing multimedia resources based on contexts towards providing a truly personalised eLearning experience. This paper presents a framework for achieving context-based multimedia semantic annotation and organisation towards personalised learning.
Keywords: Multimedia technology; Web based learning; WWW